1999
DOI: 10.1007/bf02324651
|View full text |Cite
|
Sign up to set email alerts
|

3-acyl-1,5-benzodiazepines in the reactions of 5,5-dimethyl-2-formylcyclohexane-1,3-dione with certain 1,2-diaminobenzenes

Abstract: Continuing our study of the synthesis of 3-acyl-l,5-diazepines through reaction of 2-acyicyclane-l,3diones with 1,2-diamines [I, 2] we have examined the reaction of 2-formyl-5,5-dimethylcyclohexane-l,3-diones (I) with 4-methyl-(lib), 4-benzoyi-(IIc), and 1,2-diamino-4-nitrobenzenes (IId). As shown in [2], the formylcyclanedione I and o-phenylenediamine (IIa) react in a molar ratio of 1 : 1 to give enamine IIIa. The presence of two non-equivalent amino groups in the starting diamines IIb-d makes the possible f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…To highlight the advantages of this newly developed method, we have compared the results of the current study with those reported in literature for the same transformation using different conditions [20][21][22][23][24][25] (Table 1) When the reaction was carried out under solvent-free conditions at 60 °C, the product was isolated in 55% yield ( Table 2, entry 9). Furthermore, when the reaction was conducted in the presence of 0.14 g of the [H-NMP][HSO4] catalyst at 100 °C, the desired product 3e was isolated in a 85% yield ( The results of the optimization experiments indicated that the MCR was being catalyzed much more effectively by [H-NMP][HSO4] that any of the other catalysts tested, because the desired product was obtained in much higher yields over shorter reaction times when the reaction was conducted in the presence of this IL catalyst ( Table 2, entries 1-12).…”
Section: Catalytic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…To highlight the advantages of this newly developed method, we have compared the results of the current study with those reported in literature for the same transformation using different conditions [20][21][22][23][24][25] (Table 1) When the reaction was carried out under solvent-free conditions at 60 °C, the product was isolated in 55% yield ( Table 2, entry 9). Furthermore, when the reaction was conducted in the presence of 0.14 g of the [H-NMP][HSO4] catalyst at 100 °C, the desired product 3e was isolated in a 85% yield ( The results of the optimization experiments indicated that the MCR was being catalyzed much more effectively by [H-NMP][HSO4] that any of the other catalysts tested, because the desired product was obtained in much higher yields over shorter reaction times when the reaction was conducted in the presence of this IL catalyst ( Table 2, entries 1-12).…”
Section: Catalytic Performancementioning
confidence: 99%
“…For example, 1,5-dibenzodiazepine derivatives have been reported to exhibit inhibitory activities towards hepatitis C virus (HCV) NS5B [8] and HIV-1 protease [9,10], as well as finding numerous applications in medicinal chemistry [11], where they have been used as antiinflammatory [12], hypnotic [13], anticoagulant [14], antibacterial [15], antidepressant [16], antiepileptic [17,18] and analgesic [19] agents. Several methods have been reported for the synthesis of 1,5-benzodiazepine derivatives via the condensation of o-phenylenediamine and dimedone with various aldehydes or ketones in the presence of a wide variety of Brӧnsted acid catalysts, including acyl chlorides [8,9] oxalic acid in water [20], acetic acid in refluxing ethanol [21,22], HCl in ethanol [23], acetic acid in toluene [24] and H2SO4 in water [25]. Several other methods have also been developed for the synthesis of 1,5-benzodiazepine derivatives, such as the cycloaddition reaction of 2,2-dihydroxy-1-phenylethanone with an o-phenylenediamine derivative and dimedone [26], the hetero-Cope rearrangement and the condensation of a 2-formyl benzoic acid substrate with an o-phenylenediamine derivative and tetronic acid in water under microwave irradiation conditions [27].…”
Section: Introductionmentioning
confidence: 99%